2010
DOI: 10.1242/dmm.005769
|View full text |Cite
|
Sign up to set email alerts
|

Combined zebrafish-yeast chemical-genetic screens reveal gene–copper-nutrition interactions that modulate melanocyte pigmentation

Abstract: SUMMARY Hypopigmentation is a feature of copper deficiency in humans, as caused by mutation of the copper (Cu2+) transporter ATP7A in Menkes disease, or an inability to absorb copper after gastric surgery. However, many causes of copper deficiency are unknown, and genetic polymorphisms might underlie sensitivity to suboptimal environmental copper conditions. Here, we combined phenotypic screens in zebrafish for compounds that affect copper metabolism with yeast chemical-genetic profiles to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…As the MAPK pathway plays important roles in both cell proliferation and angiogenesis (15,30), Mek protein kinases may be critical targets for Cu chelators as chemotherapeutic agents. In support of this possibility, the Mek kinase inhibitor U0126 was recently identified in a screening for compounds that affect Cu metabolism in zebrafish (23).…”
Section: Discussionmentioning
confidence: 99%
“…As the MAPK pathway plays important roles in both cell proliferation and angiogenesis (15,30), Mek protein kinases may be critical targets for Cu chelators as chemotherapeutic agents. In support of this possibility, the Mek kinase inhibitor U0126 was recently identified in a screening for compounds that affect Cu metabolism in zebrafish (23).…”
Section: Discussionmentioning
confidence: 99%
“…Copper is a key trace mineral in mink nutrition in terms of its role in hemoglobin formation and normal pigmentation of fur (Ajayi 2005;Ishizaki et al 2010). The element is also an essential component of many enzyme systems such as cytochrome C oxidase, amino oxidase, polyphenol oxidase, ferroxidase, and copper-zinc superoxiode dismutase (Gaetke and Chow 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1). Several studies applying the zebrafish model in a similar manner have recently been reported in the literature (Ishizaki et al, 2010;Behra et al, 2004;Davidson et al, 2008;Molina et al, 2009;Arslanova et al, 2010;Buckley et al, 2010;Hao et al, 2010;Kokel et al, 2010;Rihel et al, 2010). In the sections below, we summarize some of these examples to illustrate the utility of the zebrafish embryo as a promising system for detecting off-target effects of drug candidates.…”
Section: Primermentioning
confidence: 94%